289Birthweight and risks of adult-onset diabetes in women who are and are not overweight. (2nd September 2021) - Shawon, Shajedur Rahman; Yang, TienYu Owen; Floud, Sarah; Green, Jane; Reeves, Gill; Beral, Dame Valerie
Abstract: Background: Higher adult body mass index (BMI) increases diabetes risk, whereas, paradoxically, lower birthweight is associated with higher risks of adult-onset diabetes. Increased diabetes risks associated with low birthweight might be due to increased risks among those who become overweight or obese as adults but evidence on risks among those of normal BMI is limited. Methods: In the Million Women Study, 413, 516 women without prior diabetes, at mean age 60(SD5) years, reported their birthweight, and current height and weight. Birthweight and BMI at age 60 years were validated against recorded values at similar ages. Participants were followed for diabetes by electronic linkage to national hospital admissions records. Cox regression yielded multivariable-adjusted relative risks (RRs) for diabetes, overall and subdivided simultaneously by categories of birthweight and adult BMI. Results: During 15(SD3) years follow-up, 24, 528 women had hospital admissions with diabetes, first recorded at average age 70(SD6) years. Adult-onset diabetes risks increased strongly with increasing adult BMI (RR per 5 kg/m 2 increase: 2.03, 95% CI 2.01-2.06). Compared to those with birthweight 3.0-3.4 kg, RRs of diabetes for birthweight <2.5 kg and ≥4.0 kg were 1.35(1.30-1.38) and 0.73(0.70-0.75), respectively. The association between low birthweight and increased diabetes risk was strongly evident among women who were of normal BMI, overweight and obese (p < 0.0001 for each). Conclusions: At every level of adult adiposity, there were strong inverse associations between birthweight and adult-onset diabetes risk. Key messages: While adult adiposity increases diabetes risk, there is a strong and independent increase in diabetes risk with decreasing birthweight.